2015
DOI: 10.12933/therya-15-270
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual association levels correlate to behavioral diversity in coastal bottlenose dolphins (Tursiops truncatus) from the Southwestern Gulf of Mexico

Abstract: Las asociaciones entre individuos se correlacionan con la diversidad de las conductas en delfines costeros (Tursiops truncatus) del Sureste del Golfo de MéxicoInter-individual association levels correlate to behavioral diversity in coastal bottlenose dolphins (Tursiops truncatus) from the Southwestern Gulf of Mexico Introduction: Societies in mammal species are influenced by intrinsic and extrinsic factors that affect the temporality of the associations among individuals. Coastal bottlenose dolphins generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Group size in coastal bottlenose dolphins usually varies between 5 and 15 individuals (Morteo, 2011); however, smaller groups (<5 individuals) were found in the coastal waters of Alvarado. This seems typical for the studied population (Morteo, 2011), thus it has been hypothesized to constitute a strategy that reduces detectability by fishers while also decreasing the chances of negative outcomes for the dolphins (García-Vital et al ., 2015); the latter as a response to the pressure by fishers that this dolphin population has suffered for decades, which was evidenced during this study, including violent retaliation to individuals that interacted with their gear (Del Castillo-Olvera, 2010; Morteo, 2011; Morteo et al ., 2017; Rechimont et al ., 2018). Conversely, in other study areas, where human-dolphin competition for fish is not as noticeable, dolphin group sizes observed around fishing activities are mostly related to the biomass of prey captured in the gear (Lauriano et al ., 2004; Rocklin et al ., 2009).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Group size in coastal bottlenose dolphins usually varies between 5 and 15 individuals (Morteo, 2011); however, smaller groups (<5 individuals) were found in the coastal waters of Alvarado. This seems typical for the studied population (Morteo, 2011), thus it has been hypothesized to constitute a strategy that reduces detectability by fishers while also decreasing the chances of negative outcomes for the dolphins (García-Vital et al ., 2015); the latter as a response to the pressure by fishers that this dolphin population has suffered for decades, which was evidenced during this study, including violent retaliation to individuals that interacted with their gear (Del Castillo-Olvera, 2010; Morteo, 2011; Morteo et al ., 2017; Rechimont et al ., 2018). Conversely, in other study areas, where human-dolphin competition for fish is not as noticeable, dolphin group sizes observed around fishing activities are mostly related to the biomass of prey captured in the gear (Lauriano et al ., 2004; Rocklin et al ., 2009).…”
Section: Discussionmentioning
confidence: 69%
“…The adaptation of strategies for food acquisition (Sargeant & Mann, 2009), where adult male dolphins moving alone or in small groups are more frequently associated with fishing gear depredation (Adimey et al ., 2014; Morteo et al ., 2014; Labadie et al ., 2018; Rechimont et al ., 2018) has been linked to their curious and predatory behaviour, as well as their easy habituation to the varying conditions in their habitat (Adimey et al ., 2014; Morteo et al ., 2014, 2017; La Fauci, 2017). Many of these interactions have been attributed to adult males and point to the development of a sex-biased strategy to take advantage of captured fish (Morteo et al ., 2012, 2017; Garcia-Vital et al ., 2015; Rechimont et al ., 2018). Furthermore, female individuals within the population are more resident and thus experienced (Morteo et al ., 2014), and especially nursing or lactating individuals are known to avoid fishing areas (La Fauci, 2017), since these present a higher risk of injury (Srinivasan et al ., 2017), due to fishers' antagonistic responses to the encounters with bottlenose dolphins (Morteo et al ., 2012; Rechimont et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hurtado-Mejorada (2021) already found that bottlenose dolphin echolocation trains were significantly more frequent during fishing manouvers in the Alvarado area. Also, Garcıá-Vital et al (2015) found lower group sizes as a possible adaptative response to lower the risk of human retaliation during interactions with fisheris (Morales-Rincon et al, 2019). Therefore, hearing interference due to high marine traffic (e.g.…”
Section: Passive Acoustic Hypothesis Feeding Areas and Thropic Levelmentioning
confidence: 99%
“…In addition, as noted by Morteo et al (2017) and Bolaños-Jimeńez et al (2021), individual dolphins that are "new" to the area (the majority of which were presumed to be male; Morales-Rincon et al, 2019), have been found to have a higher tendency to interact with local artisanal fisheries than local residents. Furthermore, dolphins in the region reduce their group sizes and reduce their surface behaviors when interacting with gillnet fisheries (Garcıá-Vital et al, 2015;Morales-Rincon et al, 2019), presumably to lower the risk of being spotted, since they often face retaliation while interacting with local artisanal fisheries (Morteo et al, 2017;Rechimont et al, 2018). In addition, dolphin's groups may reduce their size possibly to lower intraspecific competition, and also because obtaining the resource in fishing nets is easier, so they do not need to employ cooperative hunting strategies, which also reduces interindividual competition (Methion and Dıáz Loṕez, 2020).…”
Section: Energy Content As An Indicator Of Gear Interaction and Depre...mentioning
confidence: 99%